Metode Black Box Pada Pengujian Sistem Informasi Surat Keluar Masuk - Nurul Hanifah Hasibuan; Zahra Nurhaliza (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Nowadays, it is very important to measure the quality of software before users start using the software. This is to determine the vulnerability of the system so that the data generated matches the input data after running the data. This research is an incoming and outgoing mail information system which is then subjected to black box testing. This method focuses on data entry, system display, memory usage, and data execution speed. Therefore, if the data entered is not as expected, the system will fail. The results of testing with this method are very good, because all weaknesses can be known before use.